RISK ASSESSMENT OF GAS PIPELINE CROSSING UNDER RAILWAY TRACKS AND DENSE RESIDENTIAL AREAS - Nurdiansyah, Angga; Puja , IGN Wiratmaja; Kariem, M Agus (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2025)
The crossing of Gas pipelines with railways is part of the energy transportation infrastructure that requires special attention, both to the operational safety of the pipeline and the railway line itself. Therefore, stakeholders need to conduct a risk assessment of each pipeline and railroad crossing to ensure that the risks are within safe and tolerable limits. This study aims to assess the risk at a gas pipeline crossing with a railway line in Central Java Province, Indonesia, using a quantitative risk assessment (QRA) approach with reference from the BS 8010-3:2009 +A1 2013 standard. The assessment results at the crossing showed an individual risk of 3,35x10-8/year and a societal risk in the ALARP Zone. The proposed risk mitigation can reduce the individual risk from 3,35x10-8/year to 1,12x10-8/year. However, although the risk mitigation can reduce the individual risk at the crossing location, the societal risk is still in the ALARP Region. Therefore, the crossing between the gas pipeline and the railway needs the attention, both pipeline operators and railway companies, to ensure the operational safety and security of both parties.